HOW STUDENTS SOLVE PIZZA PROBLEMS: AN EXPLORATION OF STUDENTS' MATHEMATICAL LITERACY - Nego Linuhung; Purwanto Purwanto; Sukoriyanto Sukoriyanto; Sudirman Sudirman (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The pizza problem was chosen because the question consistently appears in every activity conducted by the Program for International Student Assessment (PISA) to measure mathematical literacy. However, Indonesian students have not yet successfully solved the pizza problem correctly. The purpose of this study is to describe the mathematical literacy of students in solving pizza problems that have been adapted in the process component and differences. This study focuses on students' answers in solving pizza problems with different information in each question. Data collection was carried out using tests and interviews. The research method employed is qualitative with a descriptive approach. The research subjects were ninth-grade junior high school students. Data collection was carried out to identify students' mathematical literacy on pizza problems by analyzing the results of tests and interviews. The results showed that: 1. students had difficulty in solving pizza problems, formulating mathematical problems, performing calculations using the concept of specific formula rules, and interpreting from a precise process correctly; 2. there are differences in students' answers in solving three types of pizza problems. Students did not solve pizza problems correctly through the correct calculation and interpretation, but on type 2 questions, students performed better than the students working on the other two problems. Students can easily understand the question with more detailed explanations. Therefore, in adapting a question from a foreign language, a careful, thorough, and accurate interpretation is required.Masalah pizza dipilih karena pertanyaan tersebut selalu muncul dalam setiap kegiatan yang dijalankan oleh Program for International Student Assessment (PISA) untuk mengukur literasi matematis. Namun demikian, siswa Indonesia belum berhasil menyelesaikan masalah pizza dengan benar. Tujuan penelitian ini adalah mendeskripsikan literasi matematika siswa dalam menyelesaikan soal pizza yang telah diadaptasi pada komponen proses dan perbedaan jawaban siswa dalam menyelesaikan soal pizza yang telah diadaptasi dengan memberikan informasi yang berbeda pada setiap soal. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Subjek penelitian adalah siswa kelas 9 Sekolah Menengah Pertama. Pengumpulan data dilakukan untuk mengidentifikasi literasi matematis siswa pada soal pizza dengan menganalisis hasil tes dan wawancara. Hasil penelitian menunjukkan bahwa: 1. siswa kesulitan dalam menyelesaikan masalah pizza, siswa kesulitan dalam merumuskan masalah secara matematis, siswa belum mampu melakukan perhitungan menggunakan konsep aturan rumus tertentu; serta siswa belum mampu menafsirkan dari suatu proses matematis dengan benar; 2. terdapat perbedaan jawaban siswa dalam menyelesaikan 3 tipe soal masalah pizza yang diadaptasi, pada soal tipe 2 siswa menunjukkan kinerja lebih baik dibandingkan siswa yang mengerjakan dua soal lainnya. Oleh karena itu dalam mengadaptasi soal berbahasa asing maka harus mengartikannya dengan hati-hati, teliti dan cermat.